Autoimmune reaction against pancreatic beta cells in children and adolescents with simple obesity - Chylińska-Frątczak, Aneta; Pietrzak, Iwona; Michalak, Arkadiusz; Wyka, Krystyna; Szadkowska, Agnieszka (Frontiers in Endocrinology, 2022)
The present study assessed the prevalence of autoantibodies against pancreatic islet beta cell’s antigens in children and adolescents with simple obesity. Material and methods This prospective observational study included pediatric patients (up to 18 years of age) with simple obesity. Collected clinical data included sex, age, sexual maturity ratings, body height and weight, waist and hip circumference, amount of body fat and lean body mass. Each participant underwent a 2-hour OGTT. HbA1c, fasting and stimulated c-peptide, total cholesterol, HDL, LDL, triglycerides were measured. HOMA-IR was calculated. The autoantibodies against pancreatic islet beta cells were determined: ICA - antibodies against cytoplasmic antigens of pancreatic islets, GAD - antibodies against glutamic acid decarboxylase, ZnT8 - antibodies against zinc transporter, IA2 - antibodies against tyrosine phosphatase, IAA – antibodies against insulin. Results The study group included 161 children (57.4% boys, mean age 13.1±2.9 years) with simple obesity (mean BMI z-score +2.2±1.6). Among them, 28 (17.4%) were diagnosed with impaired glucose metabolism during OGTT [23 (82.2%) – isolated impaired glucose tolerance (IGT), 3 (10.7%) – isolated impaired fasting glucose (IFG), 2 (7.1%) – IFG and IGT]. Of the children tested, 28 (17.4%) were tested positive for at least one islet-specific autoantibody, with ICA being the most common (positive in 18, 11.2%). There was no association between the presence of the tested antibodies and age, sex, stage of puberty, parameters assessing the degree of obesity, HbA1c, lipid levels and basal metabolic rate. However, autoantibody-positive subjects were more likely to present IFG or IGT compared to those who tested completely negative (9, 32.1% vs 19, 14.3%, p=0.0280). Their HOMA-IR was also significantly higher (HOMA-IR: 4.3±1.9 vs 3.4±1.9, p=0.0203) and this difference remained statistically significant after adjusting for sex and age (p=0.0340). Conclusions Children and adolescents with simple obesity presented a higher prevalence of markers of autoimmune response against pancreatic beta cells than the general population. Most often, they had only one type of antibody - ICA. The presence of autoimmune response indicators against pancreatic islet antigens is more common in obese patients with impaired carbohydrate metabolism and is associated with lower insulin sensitivity.